Analysis of the presence of mycotoxins in swine feed and its possible effects on semen quality in a rural property of Santa Catarina - Nones, Janaína; Nones, Jader; Scussel, Vildes Maria (Revista de Ciências Agroveterinárias, 2014)
The presence of mycotoxins in swine feed can trigger off serious problems. Besides influencing the quality and quantity of semen produced, it can also cause weight loss, as well as alterations of the immune and reproductive systems. This study reports on an assessment of male swine reproductive parameters over the years 2010 to 2011, at a small rural property in Santa Catarina State, Brazil, seeking to correlate them with possible contamination of the swine’s diet by different mycotoxins. Out of a total of 12 samples of feed collected between August 2010 and February 2011, 58.3% were found to be contaminated with fumonisins (FBs). Only one sample of feed was contaminated by zearalenone (ZON) (64.10 μg kg-1). No contamination by aflatoxins (AFLs), ochratoxin A (OTA) and sterigmatocystin (EST) was detected. 75 swine semen samples were collected and analysed in relation to reproductive parameters (sperm motility, volume and density). The findings were correlated to the levels of mycotoxins in feed given to the sample donors. In spite of the levels of mycotoxin contamination found in the feed (FBs and ZON), no significant variations in sperm motility, volume or density were observed in this study.